1969
DOI: 10.1038/icb.1969.6
|View full text |Cite
|
Sign up to set email alerts
|

DISTRIBUTION OF 125I‐IMMUNOGLOBULINS, IgG SUBUNITS AND ANTIGEN‐ANTIBODY COMPLEXES IN RAT LYMPH NODES

Abstract: Summary. Tlit* ability of rahhit lf;G tn localize in Follicles of rat lympli nodes (Iifterologoiis sysU-m) lias IH'CII shown to hv tint-to tlit* i' V fragiiifnt. Of tlic-r»l)bit IyG subiinits e\:imiiu;tl, llie H chain .uul Fc fraynK-iit showed folticular localization in rats, while tlie L chain and Fa!) friij;nient did not. Two Iarf:c pfplidcs from the Fc region of tlie molecule, C3 and C4, also showed follicithir locali/ation.Human seriini albumin showed follicuhir localization in rats only when it was couipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…i-FDRCs bind Fc but not the Fab fragments of IgG and therefore seem to have an Fc receptor (Herd & Ada 1969). Tbe absence of C3 in the serum appears to have a negative influence on the localization of immune complexes in the follicles of spleen (Papamichael et aL 1975, Tew et al 1979).…”
Section: Interdigitating Reticulum Cells (Ircs)mentioning
confidence: 99%
“…i-FDRCs bind Fc but not the Fab fragments of IgG and therefore seem to have an Fc receptor (Herd & Ada 1969). Tbe absence of C3 in the serum appears to have a negative influence on the localization of immune complexes in the follicles of spleen (Papamichael et aL 1975, Tew et al 1979).…”
Section: Interdigitating Reticulum Cells (Ircs)mentioning
confidence: 99%
“…Two sorts of experiments were attempted to find out what components of an immune complex were responsible for binding to FDC's. Earlier workers emphasized the requirement for specific antibody, probably the F~ portion (16,19,21). We found that F(ab')2 anti-HRP-HRP complexes exhibited greatly reduced association with FDC's.…”
Section: Mechanism Of Immune Complex Retention On Fdc'smentioning
confidence: 99%
“…Several decades ago, it was established that deposition of immune complexes on FDCs was strongly dependent on complement [5][6][7] and the Fc portion of antibodies [7,8]. The complement receptors 1 (CD35) and -2 (CD21) were found to be highly expressed by FDCs [2].…”
Section: Introductionmentioning
confidence: 99%